Retraction Note: Islamic Psychology: Historical Notes from Herbert George Wells (1866–1946) - Çaksen, Hüseyin; Çaksen, Feyza (Journal of Pediatric Neurology, 2024)
The above article published in Journal of Pediatric Neurology on November 16, 2022 (DOI: 10.1055/s-0042-1758473), has been retracted as it is lacking scientific base.